Developing Inductive–Deductive Models with Cognitive Conflict to Enhance Students Problem-Solving and Confidence - Rusmini Rusmini; Dian Armanto; Mukhtar Mukhtar; Nuraini Sribina; Muhammad Rizky Mazaly (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The ability to solve problems in math and confidence are two crucial skills that need to be built in math learning in the 21st century. However, many students have a challenge in understanding concepts in depth and applying them to solve problems. The purpose of this study is to develop an Inductive–Deductive learning model based on the Cognitive Conflict Strategy, called Thinking in Two Directions, to improve students' mathematical problem-solving skills and confidence. This research follows the Plomp development model which consists of five stages: (1) initial research, (2) design, (3) development, (4) testing, evaluation, and improvement, and (5) implementation. The model is designed with five main steps, namely: Conceptual Identification and Conflict, Inductive Exploration, Deductive Generalization, Reflective Application, and Confirmation and Self-Evaluation. The results of validity, practicality, and effectiveness testing show that this model is valid, practical, and effective for use in mathematics learning. The Thinking in Two Directions model has been shown to be effective in improving students' ability to solve mathematical problems as well as increasing their confidence in dealing with complex mathematical problems.